Socialization of Personal Hygiene for Danu’s Tofu Home Industry Workers in Alue Peunyareng, Meureubo Subdistrict, West Aceh Regency, Aceh - Maya Indra Rasyid; Devi Agustia; Nanda Triandita; Hilka Yuliani; Lia Angraeni; Desi Susanti (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Tofu is one of the favorite foods of Indonesian people. Tofu processing has been carried out in several home industries in West Aceh Subdistrict. This community engagement program focused on the tofu home industry starting from a survey and mapping of the business condition followed by training and supervision activity. This training was given to tofu home industry owners and their workers. This training and supervision aimed to improve partners' knowledge and understanding about the importance of applying personal hygiene to the workers. Increased knowledge will in turn raise the awareness and motivation of the workers to apply personal hygiene procedures in tofu processing.